Impact of COVID-19 on cardiac procedure activity in England and associated 30-day mortality. (3rd October 2022) - Mohamed, M; Banerjee, A; Clarke, S; De Belder, M; Goodwin, A; Gale, C; Curzen, N; Mamas, M
Abstract: Background: The COVID-19 pandemic had a significant impact on the quality of healthcare provision across all specialities and disciplines. However, there are limited data on the scale of its disruption to cardiac procedure activity from a national perspective and whether procedural outcomes different before and during the COVID-19 pandemic. Methods: Major cardiac procedures (n=374, 899) performed between 1st January and 31st May for the years 2018, 2019 and 2020 were analysed, stratified by procedure type and time-period (pre-COVID: January-May 2018 and 2019 and January-February 2020 and COVID: March-May 2020). Multivariable logistic regression modelling was undertaken to examine the odds ratio (OR) of 30-day mortality for procedures performed in the COVID period (vs. pre-COVID). Results: There was a deficit of 45, 501 procedures during the COVID period compared to the monthly averages (March-May) in 2018–2019. Cardiac catheterisation and cardiac electronic device implantations were the most affected in terms of numbers (n=19, 637 and n=10, 453) while surgical procedures including mitral valve replacement, other valve replacement/repair, atrial and ventricular septal defect repair, and CABG were the most affected as a relative percentage difference (D) to previous years' averages. TAVR was the least affected (D-10.6%). No difference in 30-day mortality was observed between pre-COVID and COVID time-periods for all cardiac procedures except cardiac catheterisation (OR 1.25 95% confidence interval (CI) 1.07–1.47, p=0.006) and cardiac device implantation (OR 1.35 95% CI 1.15–1.58, p<0.001). Conclusion: There was a significant decline in national cardiac procedural activity in England during the COVID-19 pandemic, with a deficit in excess of 45000 procedures over the study period. However, there was no increase in risk of mortality for most cardiac procedures performed during the pandemic. While health service pressures are gradually easing given the increased roll out of vaccination and decline in infection rates, there is a need for major restructuring of cardiac services deal with this significant backlog of procedures, which would inevitably impact longer-term morbidity and mortality. Funding Acknowledgement: Type of funding sources: None.